Prospecting the Potential of Agroresidues as Substrate for Microbial Flavor Production - Sharma, Abha; Sharma, Pushpendra; Singh, Jyoti; Singh, Surender; Nain, Lata (Frontiers in Sustainable Food Systems, 2020)
With the growing consumer demand for natural food products, including food flavors, efforts towards identifying biotechnological interventions for their production have increased tremendously. The present paper reviews the production of flavor compounds by microbial biosynthesis or biotransformation, and their enzymes involved in synthesis and conversion from progenitor substrates. More importantly, the use of abundant, inexpensive, and nutrient-rich lignocellulosic waste generated by the processing set-ups of agro-industries as a potential substrate for the microbial production of flavor compounds under solid-state fermentation is reviewed. The article provides insights regarding the development of an efficient and cost-effective process to produce important flavors from agroresidues. The biotechnological route will also help in safe and eco-friendly management of wastes generated from agriculture.